Preservation of Javanese Language in Islamic Boarding School Learning as a Strengthener of the Paradigm of Conservatism and Traditionalism in Islamic Education - Zakiya Very Ayu Suryatina; Muhlisin Muhlisin; M. Sugeng Solehudin; Fatah Syukur; Asnalia Rokhmah (Academia Open, 2026)
General Background: Regional languages play a crucial role in shaping cultural identity and educational traditions within Indonesian Islamic institutions. Specific Background: In traditional Islamic boarding schools (pesantren) in Java, the Javanese language has long functioned as a medium for learning classical Islamic texts, moral education, and daily interaction, particularly within salafiyah pesantren. Knowledge Gap: Despite extensive discussions on pesantren and local culture, limited scholarly attention has been given to Javanese language preservation as a core mechanism reinforcing conservatism and traditionalism in Islamic education amid modernization. Aims: This study aims to examine how the preservation of the Javanese language in pesantren learning practices strengthens paradigms of conservatism and traditionalism in Islamic education. Results: Using a qualitative case study approach in three traditional pesantren in Central Java, the findings show that Javanese functions as a pedagogical medium, a transmitter of adab, hierarchy, and scholarly authority, and a cultural strategy to maintain traditional Islamic values. Novelty: This study positions Javanese language preservation not merely as cultural maintenance but as an epistemological foundation sustaining conservative and traditional Islamic educational paradigms. Implications: The findings highlight the importance of integrating local language preservation into Islamic education policies to sustain moral formation, cultural identity, and continuity of classical Islamic traditions alongside selective educational adaptation. Highlights: Javanese serves as a primary medium for transmitting classical Islamic knowledge and moral values. Language practices reinforce hierarchy, adab, and scholarly authority within boarding school communities. Linguistic maintenance operates as a cultural strategy amid educational modernization pressures. Keywords : Javanese Language Preservation, Pesantren Education, Islamic Conservatism, Educational Traditionalism, Local Culture